2013
DOI: 10.1016/j.critrevonc.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The key role of growth hormone–insulin–IGF-1 signaling in aging and cancer

Abstract: Studies in mammals have led to the suggestion that hyperglycemia and hyperinsulinemia are important factors in aging. GH/Insulin/insulin-like growth factor 1 (IGF-1) signaling molecules that have been linked to longevity include daf-2 and InR and their homologues in mammals, and inactivation of the corresponding genes increases lifespan in nematodes, fruit flies and mice. The life-prolonging effects of caloric restriction are likely related to decreasing IGF-1 levels. Evidence has emerged that antidiabetic dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 207 publications
4
126
0
3
Order By: Relevance
“…These effects are similar to those evoked by calorie restriction and by germline mutations that compromise GH/IGF-I signaling-which typically slow aging, prevent cancer, and boost maximal lifespan (Bartke 2008;Brown-Borg et al 2009;Anisimov and Bartke 2013).…”
mentioning
confidence: 84%
“…These effects are similar to those evoked by calorie restriction and by germline mutations that compromise GH/IGF-I signaling-which typically slow aging, prevent cancer, and boost maximal lifespan (Bartke 2008;Brown-Borg et al 2009;Anisimov and Bartke 2013).…”
mentioning
confidence: 84%
“…13 In a number of studies it was shown that administration of antidiabetic biguanides (phenformin, buformin and metformin) started at adult age increased life span and suppressed spontaneous and induced tumorigenesis. 2,[34][35][36][37][38] It is worthy to note that male and female adult 129/Sv mice demonstrated divergent reaction to the same dose of metformin. Metformin failed to increase life span of male F344 rats.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This leads to a conclusion that the normal levels and physiological actions of GH are not optimal for disease-free survival or for longevity. Since GH is key determinant of circulating levels of insulin-like growth hormone-1 (IGF-1) and it also increases insulin levels as a secondary consequence of its anti-insulinemic actions, conclusions concerning GH and normal aging extend to the roles of IGF-1 and insulin in this process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations